2015
DOI: 10.1148/radiol.15142009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Availability of Prior Full-Field Digital Mammography and Digital Breast Tomosynthesis Images on the Interpretation of Mammograms

Abstract: Purpose:To assess the effect of and interaction between the availability of prior images and digital breast tomosynthesis (DBT) images in decisions to recall women during mammogram interpretation. Materials and Methods:Verbal informed consent was obtained for this HIPAA-compliant institutional review board-approved protocol. Results:Average recall rates in noncancer cases were significantly reduced with the addition of prior FFDM images by 34% (145 of 421) and 32% (106 of 333) without and with DBT images, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The use of prior mammograms in the reading of current mammograms had previously been reported to increase specificity especially in the screening setting (13,15), while also increasing the detection of true-positive findings in the diagnostic setting (1). Current studies by Hakim et al also reported that recall rates were able to be reduced with the addition of prior images by 34% and 32% without and with DBT images (16,17) although their study did not describe the effect of prior mammograms on diagnostic performance in terms of sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 98%
“…The use of prior mammograms in the reading of current mammograms had previously been reported to increase specificity especially in the screening setting (13,15), while also increasing the detection of true-positive findings in the diagnostic setting (1). Current studies by Hakim et al also reported that recall rates were able to be reduced with the addition of prior images by 34% and 32% without and with DBT images (16,17) although their study did not describe the effect of prior mammograms on diagnostic performance in terms of sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 98%
“…However, even experienced radiologists sometimes fail to interpret the images correctly. [ 37 , 38 ] To reduce this failure, physical factors that can affect the comparison performance need to be analyzed beforehand. Following the same line of thought, analyzing the effect of the change in object position should precede the comparison of follow up CBCT images.…”
Section: Discussionmentioning
confidence: 99%
“…Although 92% of radiologists were within the recommended ranges for sensitivity, only 63% achieved the recommended levels of specificity . The sensitivity and specificity of mammography are improved if prior studies are available to the interpreting physician . Hayward et al evaluated outcomes of over 46,000 consecutive mammograms and observed a recall rate 16.6% when prior examinations were not compared, but the rate was only 7.8% when 1 prior examination was available for comparison, and it was 6.3% when 2 or more prior examinations were available .…”
Section: Breast Cancermentioning
confidence: 99%
“…60,[66][67][68][69][70] The sensitivity and specificity of mammography are improved if prior studies are available to the interpreting physician. 71,72 Hayward et al evaluated outcomes of over 46,000 consecutive mammograms and observed a recall rate 16.6% when prior examinations were not compared, but the rate was only 7.8% when 1 prior examination was available for comparison, and it was 6.3% when 2 or more prior examinations were available. 71 A statistically significant improvement in the cancer detection rate of 2.3 cases per 1000 examinations also was observed for mammograms that were interpreted with multiple prior examinations versus a single prior examination.…”
Section: Benefits Limitations and Harmsmentioning
confidence: 99%